Read my lips [lip-syncing]. - Costlow, T.
Engineers at Kyungpook National University in Daegu, South Korea, have come up with a way of embedding an easy-to-read test signal that can be run during normal broadcasts. They embedded the test signal in the part of the video signal that is not normally displayed on televisions and, similarly, embedded an audio marker in the part of the digital audio signal used for transmitting in multiple languages. They then came up with a way of measuring the difference between the signals with an ordinary oscilloscope instead of the special equipment, so broadcasters can make adjustments more frequently and for less money.
Keywords: Audio signals; Digital video broadcasters; Lip-syncing.; Ordinary oscilloscope; Video signals